Dual-target immunotherapies in NSCLC: a systematic review and meta-analysis of randomized clinical trials - Zhang, Yike; Wang, Haozhe; Yang, Xinyue; Lei, Changhai (Frontiers in Immunology, 2025)
BackgroundDespite advances in targeted therapies and immune checkpoint inhibitors (ICIs), the prognosis for advanced non-small cell lung cancer (NSCLC) remains poor. Bispecific antibodies (BsAbs) represent an emerging class of dual-target immunotherapies, yet their comparative efficacy and safety profiles lack comprehensive quantitative synthesis.MethodsThis systematic review and meta-analysis (PROSPERO CRD420251005168) adhered to PRISMA guidelines. We systematically searched PubMed, Web of Science, Scopus, and Embase through March 2025 for phase III randomized controlled trials (RCTs) comparing dual-target immunotherapies with conventional therapies in advanced NSCLC. Primary outcomes were progression-free survival (PFS) and overall survival (OS); secondary outcomes included objective response rate (ORR), disease control rate (DCR), and treatment-related adverse events (AEs). Risk of bias was assessed using Cochrane RoB 2.0. Random-effects models were used for data synthesis.ResultsSix RCTs (n=3,063 patients) were included. Dual-target immunotherapies significantly improved PFS (HR= 0.58, 95% CI: 0.43-0.78; p<0.001) and ORR (RR=1.29,95%CI: 1.01-1.64; p=0.04) compared to conventional therapies. No significant OS (HR=0.84,95% CI: 0.68-1.05; p=0.13) or DCR (RR=1.09, 95% CI: 0.92-1.30; p=0.30) benefits were observed. Subgroup analyses stratified by mechanism showed no statistically significant differences in efficacy and safety between dual-target immunotherapies with different targets of action. Safety analyses revealed increased risks of any adverse events (RR=1.05; 95%CI: 1.02-1.09), grade≥3 AEs (RR=1.63; 95% CI: 1.37-1.94), serious AEs (RR=1.49; 95%CI:1.31-1.69) and AEs leading to treatment discontinuation (RR=2.49; 95% CI: 1.72-3.62) with dual-target immunotherapies.ConclusionOur findings, based on phase III RCTs, are limited by substantial heterogeneity among included studies. Dual-target immunotherapies demonstrate superior PFS and ORR in NSCLC but are associated with increased toxicity, particularly with EGFR/MET-targeted agents. While offering a promising therapeutic advance, safety optimization and biomarker-driven patient selection are critical for clinical translation. Further trials are needed to validate long-term survival benefits and refine risk-benefit profiles.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251005168.